Gangguan Kecemasan Masa Remaja sebagai Sumber Ide Penciptaan Karya Seni Lukis - Dewi, Maria Ruswita; Kurniawati, Dyah Yuni (Institut Seni Indoensia Surakarta, 2023)
The idea raised in this paper is Anxiety Disorder. Anxiety disorders experienced by the author since her youh until now. Anxiety disorders arise from past trauma due to bullying in the family and in society. Anxiety disorders which experienced by the author are related to excessive fear and anxiety accompanied by behavioral disorders. Events that are imprinted on the memory give rise to noisy thoughts and feelings. The problems to discuss in this article with the following. problem formulation are 1) What is an anxiety disorder 2) Why the concept of anxiety disorder is the source of the idea of creating a painting 3) How is the visualization of a painting with the concept of an anxiety disorder as the source of the idea for creating a work of art. The purpose of this Art Creation Thesis is to be the concept of painting creation that visualized by a drawing technique using drawing pen and charcoal on linen paper. Black and white works are applied to convey thoughts, feelings and everyday experiences. The works present using black frames with passepartout along with performance art video. Performance art that includes in this artwork is to be used as a medium to convey honesty through the body. This art work creation practice produces novelty in terms of the concepts, techniques and presentation.Keywords: Anxiety Disorder, Art Painting, Drawing Techniques.